Perspectives in clinical microbiology for combating multi-drug resistant bacterial infections - de Oliveira, André Mauricio; de Castro, Camila Prósperi (Frontiers in Cellular and Infection Microbiology, 2025)
Multidrug-resistant bacterial infections are a major global threat, exacerbated by globalization and poor sanitation. Bacteria develop resistance through mechanisms like enzymatic degradation, efflux pumps, and horizontal gene transfer. Rapid diagnostics and artificial intelligence are crucial for overcoming the limitations of traditional culture methods. Combating this issue requires novel therapeutic strategies, such as bacteriophages, antimicrobial peptides, and microbiome-based therapies. Ultimately, proper antibiotic use, increased research, and global multidisciplinary cooperation are essential to address this complex challenge.